(untitled) (Global Journal of Medical Research, 2014)
This paper focuses on the media reportage of the Ebola Virus Disease which has ravaged parts of West Africa, particularly Liberia, Sierra Leone and Guinea. Although the disease found its way into Nigeria through the Late Patrick Sawyer, Nigerian authorities quickly arrested the situation, for which they are getting well deserved commendations across the globe. The presentation derives its theoretical relevance from the agenda setting perspective which says that even though the media may not succeed in telling people what to think, they are stunningly successful in telling people what to think about. Information and perspectives were obtained from secondary sources of books, newspapers, magazines, and the electronic media. Interestingly, the research found a high success rate of communication efforts as it concerns the Ebola scourge, across cultural and geographical boundaries. The paper recommends among others, the immortalization of Late Dr. Stella Adadevoh for her sacrifice while ensuring that the war against Ebola is sustained through a further enhancement of public enlightenment.